Perceived Strain Due to COVID-19-Related Restrictions Mediates the Effect of Social Needs and Fear of Missing Out on the Risk of a Problematic Use of Social Networks - Wegmann, Elisa; Brandtner, Annika; Brand, Matthias (Frontiers in Psychiatry, 2021)
The occurrence of the COVID-19-virus led to drastic short-term measures to reduce its spread and influence. Regulations such as "physical distancing", mentioned as “social distancing”, and the closure of public facilities during the lockdown could be perceived as burdensome especially by individuals who feel a strong need for social exchange and belonging. These components such as need to belong and the fear of missing out also play a major role in the development and maintenance of a problematic use of social networks. Researchers have argued recently that an increase of addictive (online) behaviors may be a likely consequence of subjectively experienced restrictions in the context of the COVID-19 pandemic. The current study investigates the interplay of perceived strain due to COVID-19-related restrictions and the fear of missing out (FoMO) as well as of symptoms of problematic social-networks use. We hypothesized that perceived strain due to COVID-19-related restrictions mediates the effect of specific predisposing variables related to social needs on the symptom severity of a problematic use. To assess the perceived strain due to COVID-19-related restrictions, we developed a specific questionnaire asking for perceived COVID-19-related strain in several domains of everyday-life. An exploratory factor analysis identified five factors: perceived strain related to restrictions of 1) social contacts, 2) travel, 3) childcare, 4) work, and 5) own health. In a sample of 719 German participants and data collection during the first COVID-19 lockdown (March 30th until April 3rd 2020), a structural equation model was calculated showing that higher levels of need to belong and FoMO increase perceived COVID-19-related strain, which is related to symptoms of a problematic social-networks use. The effect of need to belong on problematic social-networks use is mediated by experienced COVID-19-related strain and FoMO-online. Even if the use of social networks is not pathological per se, it may be associated with suffering for a vulnerable part of users. We conclude that specific needs and fear-associated predisposing variables contribute to experiencing physical distance and other pandemic-related restrictions as more stressful, which may increase problematic social-networks use and potentially other addictive behaviors as well in the context of the COVID-19-related lockdown.